2006
DOI: 10.1038/nature04968
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance brain–computer interface

Abstract: Video LegendsThese videos show the behavioral conditions from our different experiments. The experiment room itself was visibly dark, but the video camera could image the scene with infrared light. Bright text and numbers were added as annotations and were not seen by the monkey. Each successful trial was followed by a juice reward, indicated by a short tone followed by a click corresponding to the action of a juice dispenser. These auditory signals were heard by the monkey during the experiment. For the durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
469
3
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 623 publications
(488 citation statements)
references
References 21 publications
9
469
3
7
Order By: Relevance
“…We made two changes: (1) we ignored Baseline, since it provided no information about the target and (2) for Plan and Go, we used data within [150,350] ms after the start of each period instead of [50,250] ms as before. This further delay in the time window reflects the additional time required for plan activity to fully form and stabilize in PMd, as discussed above in association with our recent fixed-pace results (termed T skip in Santhanam et al (2006); and normalized variance reduction time in Churchland et al (2006c)). As with the state detection model, we measured the mean and variance of the neuron spike counts for each target during both Plan and Go periods.…”
Section: The Target Estimatormentioning
confidence: 78%
See 2 more Smart Citations
“…We made two changes: (1) we ignored Baseline, since it provided no information about the target and (2) for Plan and Go, we used data within [150,350] ms after the start of each period instead of [50,250] ms as before. This further delay in the time window reflects the additional time required for plan activity to fully form and stabilize in PMd, as discussed above in association with our recent fixed-pace results (termed T skip in Santhanam et al (2006); and normalized variance reduction time in Churchland et al (2006c)). As with the state detection model, we measured the mean and variance of the neuron spike counts for each target during both Plan and Go periods.…”
Section: The Target Estimatormentioning
confidence: 78%
“…With these limits identified, we can now design complementary state estimators which use trial timing parameters identified in Santhanam et al (2006) yet maintain overall prosthetic performance.…”
Section: Bci Operation Without State Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain-machine interface field has been dominated by applications in which neural signals recorded from motor or premotor areas are used to predict kinematic signals: the position of a cursor on a computer screen (Serruya et al 2002, Taylor et al 2002, Santhanam et al 2006, Kennedy and Bakay 1998, Wolpaw and McFarland 2004 or the endpoint of a robotic limb (Serruya et al 2002, Chapin et al 1999, Taylor et al 2003, Carmena et al 2003. We have demonstrated that similar techniques can be used to predict the activity of individual muscles of the arm and hand.…”
Section: Prediction Of Kinetic Signalsmentioning
confidence: 98%
“…12,16 Ongoing studies in a number of laboratories are working toward achieving natural control of devices such as a prosthetic arm using electrode microarrays implanted in the motor cortex or other cortical areas of nonhuman primates. [109][110][111][112][113][114] Plans are under way in several centers to translate these studies into human trials.…”
Section: Bcis That Use Activity Recorded Within the Brainmentioning
confidence: 99%